Nebulised antipseudomonal antibiotic therapy in cystic fibrosis: a meta-analysis of benefits and risks. Issue 4 (April 1996) - Mukhopadhyay, S; Singh, M; Cater, J I; Ogston, S; Franklin, M; Olver, R E
Abstract : BACKGROUND: To establish the benefits and risks of nebulised antipseudomonal therapy in cystic fibrosis the results of relevant randomised controlled trials were combined. METHODS: The therapeutic end points compared were (a) number of pulmonary exacerbations requiring treatment with systemic antibiotics, (b) measurable alteration in respiratory tract pseudomonal load, (c) alteration in lung function on spirometric assessment, (d) development of resistance in respiratory tract Pseudomonas strains to the nebulised antipseudomonal used in each randomised controlled trial, and (e) renal and auditory impairment. RESULTS: Five studies were suitable for meta-analysis, eight others could not be included because of inadequate outcome description or the lack of appropriate randomisation. Meta-analysis shows benefit for nebulised antipseudomonal antibiotic therapy with no demonstrable adverse effect other than a possible increase in in vitro antibiotic resistance of Pseudomonas aeruginosa of the respiratory tract. CONCLUSIONS: Although inferences drawn from individual randomised controlled trials concerning the benefits and risks of this form of therapy are conflicting, pooled effect size establishes benefit with nebulised antipseudomonal antibiotic therapy and emphasises its relevance to the integration of information in other areas of controversy relating to the treatment of this disease.